Change and Development in Nyadran Ritual Tradition in Yogyakarta - baskara, benny; Tasha F, Vincamira; Muhammad, Ali AKbar (Khatulistiwa, 2019)
The nyadran ritual is a ritual that usually conducted by Javanese Muslim to welcome Ramadhan or fasting month in the Islamic calendar. The essential element of the nyadran ritual is visiting the graveyard to clean up the grave and praying for the ancestors buried in the grave. However, in recent development, it seems that change and development are already happened to the nyadran ritual in some of its elements, such as reciting prayer together, parading the offerings to the graveyard, and end up with communal feast. The media construction is also influential, with the coverage of the nyadran ritual in Makam Sewu by various media, such as television, print media, and online media.